Governance: Making Institutions work for rural revitalization - Kosec, Katrina; Resnick, Danielle (International Food Policy Research Institute, 2019)
Investing in three aspects of governance, examined in this chapter, is critical for rural revitalization. First, appropriate and predictable laws and regulations are fundamental to economic growth and development. These laws can have unexpected and far-reaching impacts. For example, policies to reduce women’s domestic workload and to improve their access to financial and agricultural services will give women greater ability to make life choices. Rural institutions are also key: when rural government workers have adequate technical skills, financial resources, and appropriate organizational structures, they can help realize rural policy goals. Finally, accountability-from frontline civil servants to elected politicians-is essential to ensuring that governments respond to the needs of the poor.